A consensus‐based practical and daily guide for the treatment of acne patients. (14th May 2016) - Gollnick, H.P.; Bettoli, V.; Lambert, J.; Araviiskaia, E.; Binic, I.; Dessinioti, C.; Galadari, I.; Ganceviciene, R.; Ilter, N.; Kaegi, M.; Kemeny, L.; López‐Estebaranz, J.L.; et al.
Abstract: Background: Many current guidelines provide detailed evidence‐based recommendations for acne treatment. Objective: To create consensus‐based, simple, easy‐to‐use algorithms for clinical acne treatment in daily office‐based practice and to provide checklists to assist in determining why a patient may not have responded to treatment and what action to take. Methods: Existing treatment guidelines and consensus papers were reviewed. The information in them was extracted and simplified according to daily clinical practice needs using a consensus‐based approach and based on the authors' clinical expertise. Results: As outcomes, separate simple algorithms are presented for the treatment of predominant comedonal, predominant papulopustular and nodular/conglobate acne. Patients with predominant comedonal acne should initially be treated with a topical retinoid, azelaic acid or salicylic acid. Fixed combination topicals are recommended for patients with predominant papulopustular acne with treatment tailored according to the severity of disease. Treatment recommendations for nodular/conglobate acne include oral isotretinoin or fixed combinations plus oral antibiotics in men, and these options may be supplemented with oral anti‐androgenic hormonal therapy in women. Further decisions regarding treatment responses should be evaluated 8 weeks after treatment initiation in patients with predominant comedonal or papulopustular acne and 12 weeks after in those with nodular/conglobate acne. Maintenance therapy with a topical retinoid or azelaic acid should be commenced once a patient is clear or almost clear of their acne to prevent the disease from recurring. The principal explanations for lack of treatment response fall into 5 main categories: disease progression, non‐drug‐related reasons, drug‐related reasons, poor adherence, and adverse events. Conclusion: This practical guide provides dermatologists with treatment algorithms adapted to different clinical features of acne which are simple and easy to use in daily clinical practice. The checklists to establish the causes for a lack of treatment response and subsequent action to take will facilitate successful acne management.